Aspergillus oryzae accelerates the conversion of ergosterol to ergosterol peroxide by efficiently utilizing cholesterol - Qiu, Shangkun; Liu, Qicong; Yuan, Ya; Zhou, Hong; Zeng, Bin (Frontiers in Genetics, 2022)
It is well-known that excessive cholesterol leads to hypercholesterolemia, arteriosclerosis, coronary heart disease, stroke, and other diseases, which seriously threatens human health. Lactobacillus, a prokaryote, is reported to utilize cholesterol in the environment. However, little research focuses on the cholesterol utilization by eukaryote. Hence, the objectives of the present study were to investigate the mechanism of cholesterol utilization by the eukaryote and determine the role of oxysterol binding protein in this process. Our results showed for the first time that Aspergillus oryzae, a food-safe filamentous fungus, can utilize cholesterol efficiently. Our results also demonstrated that cholesterol utilization by Aspergillus oryzae might promote the conversion of ergosterol to ergosterol peroxide. Osh3, an oxysterol binding protein, can bind sterols (e.g., cholesterol, ergosterol, ergosterol peroxide) and plays an important role in sterols transportation. This research is of considerable significance for developing low-fat food and cholesterol-lowering probiotic.